A high-weather-resistant waterproof coating for a metal roof and a preparation method thereof

CN122917583APending Publication Date: 2026-10-16CHENGDU SHUYU CONSTRUCTION WATERPROOF ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611261153.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]有鉴于此,本发明提供了一种用于金属屋面的高耐候防水涂料及其制备方法,旨在解决现有金属屋面防水涂料耐候性不足、耐水性差、耐沾污性不佳、综合性能难以兼顾的技术问题

Benefits of technology

[0035](1)通过有机硅改性丙烯酸酯核壳复合乳液的设计,从基料层面提升了涂料的耐候性、耐热性和疏水性,Si-O键的高键能赋予涂膜优异的抗紫外光降解能力;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of waterproof coating and discloses a high-weather-resistance waterproof coating for metal roof and a preparation method thereof.The coating comprises a silicone-acrylate composite emulsion, a hydrophobic modified dispersant, reactive nano-zinc oxide, a silane coupling agent, a composite crosslinking agent, an ultraviolet light absorber, a hindered amine light stabilizer and a composite filler.The organic silicon-acrylate core-shell structure design of the silicone-acrylate composite emulsion, the triple crosslinking network formed by the reactive nano-zinc oxide, the silane coupling agent and the composite crosslinking agent, the synergistic hydrophobic effect of the hydrophobic modified dispersant and the light stabilizing system formed by the ultraviolet light absorber and the hindered amine light stabilizer realize the comprehensive improvement of the weather resistance, water resistance, stain resistance, mechanical property and corrosion resistance of the coating, the artificial aging resistance time of the coating can reach more than 3000 hours and the coating is suitable for long-acting waterproof protection of various metal roofs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waterproof coating technology, and more specifically to a metal roof waterproof coating that uses silicone-acrylic composite emulsion as a base material and achieves high weather resistance, high waterproof performance, and high stain resistance through raw material compounding modification and multi-component synergistic effect. Background Technology

[0002] Metal roofing is widely used in industrial plants, warehousing and logistics facilities, and large public buildings. Because metal roofing is exposed to the outdoor environment for extended periods, it is subjected to the combined effects of multiple aging factors, including ultraviolet radiation, temperature fluctuations (-30℃ to 80℃), rainwater erosion, and acid and alkali corrosion. This places extremely high demands on the weather resistance, water resistance, mechanical properties, and corrosion resistance of waterproof coatings.

[0003] Currently, waterproof coatings for metal roofs mainly include acrylic, polyurethane, silicone, and asphalt types. Among them, acrylic waterproof coatings are the most widely used due to their advantages such as being water-based, environmentally friendly, easy to apply, and having a moderate cost. However, existing acrylic waterproof coatings have the following prominent problems: (1) The weather resistance of single acrylic emulsions is insufficient, and the artificial aging time is generally less than 1500 hours, which is difficult to meet the service life requirement of more than 10 years for metal roofs; (2) The water resistance of the coating film is poor, and blistering and delamination are prone to occur in areas with water accumulation; (3) The stain resistance is poor, and white or light-colored coatings gradually become stained and dark after 1-2 years of use, affecting the reflective heat insulation effect; (4) The adhesion and anti-corrosion performance to metal substrates need to be improved.

[0004] Therefore, how to achieve a comprehensive improvement in the weather resistance, water resistance, stain resistance, mechanical properties, and corrosion resistance of metal roofing waterproof coatings without significantly increasing costs through systematic raw material compounding modification and multi-component synergistic design is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] In view of this, the present invention provides a high weather-resistant waterproof coating for metal roofs and its preparation method, aiming to solve the technical problems of insufficient weather resistance, poor water resistance, poor stain resistance, and difficulty in achieving comprehensive performance in existing metal roof waterproof coatings.

[0006] One objective of this invention is to provide a highly weather-resistant and waterproof coating for metal roofs, comprising the following components in parts by weight:

[0007] The composition includes: 350-550 parts silicone-acrylic composite emulsion, 5-15 parts hydrophobic modified dispersant, 5-30 parts reactive nano zinc oxide, 2-8 parts silane coupling agent, 1-5 parts composite crosslinking agent, 0.5-2 parts ultraviolet light absorber, 0.3-1 parts hindered amine light stabilizer, 200-350 parts composite filler, 2-4 parts defoamer, 5-15 parts film-forming aid, 10-20 parts antifreeze, 1-5 parts methacrylic acid, 3-5 parts thickener, and 100-150 parts deionized water.

[0008] Preferably, the silicone-acrylic composite emulsion is an organosilicon-modified acrylate core-shell composite emulsion, which is prepared by seed emulsion polymerization of vinyl-containing organosilicon monomers and acrylate monomers. The organosilicon monomers account for 5%-15% of the total mass of the monomers, the mass ratio of the core layer monomers to the shell layer monomers is 1:0.8-1.2, the glass transition temperature is -40℃ to -20℃, the solid content is 45%-55%, and the particle size is 80-150nm.

[0009] Preferably, the vinyl-containing organosilicon monomer is one or more of vinyltrimethoxysilane (A-171) and vinyltriethoxysilane (A-151); the acrylate monomer is one or more of butyl acrylate, methyl methacrylate, and 2-ethylhexyl acrylate.

[0010] This invention uses a silicone-modified acrylate core-shell composite emulsion as the main film-forming substance. While traditional pure acrylic emulsions possess good film-forming properties and flexibility, the ester bonds in their molecular chains are prone to hydrolysis and photodegradation under ultraviolet light and moisture, leading to accelerated coating aging. This invention utilizes a silicone-acrylate composite emulsion with a core-shell structure.

[0011] The Si-O bond energy in organosilicon monomers is significantly higher than that of C-C and CO bonds. Introducing organosilicon components results in high-energy Si-O-Si segments in the emulsion polymer backbone, significantly improving the polymer's thermal and UV stability. The core-shell structure design allows the organosilicon components to accumulate in the shell layer, preferentially exposing them to the coating surface and forming a hydrophobic protective layer. Simultaneously, the core layer maintains the flexibility of the acrylate, achieving a balance between weather resistance and flexibility. Furthermore, the alkoxy groups in the organosilicon components undergo hydrolysis and condensation reactions during film formation, forming a -Si-O-Si-inorganic network structure, further enhancing the crosslinking density and water resistance of the coating.

[0012] This invention controls the proportion of organosilicon monomers to 5%-15% of the total monomer mass. When the organosilicon content is below 5%, the improvement in weather resistance is not significant; when the content exceeds 15%, the film-forming properties and storage stability of the emulsion decrease. The mass ratio of core layer monomers to shell layer monomers is controlled at 1:0.8-1.2 to ensure the integrity of the core-shell structure and the balance of performance.

[0013] Preferably, the hydrophobic modified dispersant is a mixture of hydrophobic modified polycarboxylate dispersant and organosilicon modified polyether dispersant in a mass ratio of 2-4:1; the hydrophobic modified polycarboxylate dispersant is Rohm and Haas OROTAN 731A or Haichuan Chemical HC-5020; the organosilicon modified polyether dispersant is BYK-190 or Dispers 670.

[0014] Preferably, the reactive nano-zinc oxide has a particle size of 20-50 nm and a specific surface area greater than 80 m². 2 / g, the surface is pretreated with a silane coupling agent, the silane coupling agent used in the pretreatment is KH-570, and the amount of KH-570 is 1%-3% of the mass of nano zinc oxide.

[0015] Preferably, the silane coupling agent is one or more of γ-aminopropyltriethoxysilane (KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), and γ-methacryloyloxypropyltrimethoxysilane (KH-570); the composite crosslinking agent is a mixture of triallyl isocyanurate (TAIC) and trimethylolpropane trimethacrylate (TMPTMA) in a mass ratio of 1-3:1.

[0016] This invention constructs a triple crosslinking network system of reactive nano-zinc oxide-silane coupling agent-composite crosslinking agent. Through the synergistic reaction of the three types of active components, a dense three-dimensional crosslinking network is formed inside the coating film, significantly improving the mechanical properties, heat resistance, weather resistance, and water resistance of the coating film.

[0017] The nano zinc oxide used in this invention has dual functions: firstly, it can effectively scatter and absorb ultraviolet rays, with an ultraviolet shielding rate of over 98%, thus physically protecting the coating from ultraviolet degradation; secondly, the active hydroxyl groups on the surface of nano zinc oxide can undergo condensation reactions with the alkoxy groups of silane coupling agents, forming chemical bonds with polymer molecular chains. At the same time, nano zinc oxide can catalyze the hydrolysis and condensation reactions of silane coupling agents, accelerating the formation of cross-linked networks.

[0018] The silane coupling agents selected in this invention (such as KH-550, KH-560, and KH-570) possess dual reactive functional groups. Their alkoxy end (-Si(OR)3) can hydrolyze to generate silanol groups (-Si(OH)3), which undergo condensation reactions with the hydroxyl groups on the surface of nano-zinc oxide and the surface of the metal substrate, forming MO-Si covalent bonds (M being a metal atom or a zinc atom on the surface of nano-zinc oxide). Their organic functional group ends (amino, epoxy, or methacryloyloxy) can chemically react with the carboxyl and ester groups on the acrylate polymer chain or form hydrogen bonds. Therefore, the silane coupling agent acts as a "molecular bridge" in the coating film, connecting the inorganic nanoparticles, the metal substrate, and the organic polymer through chemical bonds, significantly improving the adhesion, water resistance, and durability of the coating film.

[0019] This invention employs a compounding of TAIC (tallyl isocyanurate) and TMPTMA (trimethylolpropane trimethacrylate) at a mass ratio of 1-3:1. TAIC molecules contain three allyl groups, and its homopolymer exhibits excellent heat resistance and electrical insulation, enabling it to undergo graft copolymerization with acrylate emulsions, forming crosslinking bridges between polymer molecular chains. TMPTMA molecules contain three methacrylate groups, exhibiting higher reactivity and allowing for copolymerization and crosslinking with acrylate monomers. When used in combination, TAIC provides heat resistance and long-term stability, while TMPTMA provides rapid crosslinking and high crosslinking density, creating complementary advantages. Furthermore, the composite crosslinking agent can also copolymerize with the organic functional groups of silane coupling agents, immobilizing the "molecular bridge" structure of the silane coupling agent and forming a more stable triple crosslinking network.

[0020] The technical principle of the triple crosslinking network: During the coating preparation and film formation process, the active sites on the surface of reactive nano-zinc oxide undergo a condensation reaction with the alkoxy groups of the silane coupling agent (Zn-O-Si bond). The organic ends of the silane coupling agent undergo a copolymerization reaction with the allyl / methacrylate groups of the composite crosslinking agent. The multifunctional groups of the composite crosslinking agent undergo a crosslinking reaction with the acrylate polymer chains, thereby constructing a triple crosslinking network inside the coating film, with nano-zinc oxide as inorganic nodes, silane coupling agent as connecting arms, and composite crosslinking agent as organic crosslinking points. This network structure significantly increases the crosslinking density of the coating film, endowing it with excellent mechanical properties (tensile strength, elongation at break), heat resistance, water resistance, and weather resistance.

[0021] Preferably, the ultraviolet light absorber is one or both of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole (UV-329) and 2-hydroxy-4-n-octyloxybenzophenone (UV-531); the hindered amine light stabilizer is one or both of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (Tinuvin 770) and bis-1,2,2,6,6-pentamethyl-4-piperidinol sebacate (Tinuvin 292); and the mass ratio of the ultraviolet light absorber to the hindered amine light stabilizer is 1.5-3:1.

[0022] This invention constructs a composite photostable system of ultraviolet light absorber (UVA) and hindered amine light stabilizer (HALS). UVA absorbs short-wave ultraviolet light (290-370 nm), which has the greatest destructive effect on coatings, through intramolecular hydrogen bonding and releases it as harmless long-wave radiation (heat). Its mechanism of action is based on photoinduced tautomerism (such as the keto-enol tautomerism of benzotriazoles), reducing the damage of ultraviolet light to polymer chains at the source. Hindered amine light stabilizer (HALS) itself does not absorb ultraviolet light, but its piperidine group can be converted into nitroxide radicals (>NO·) under light conditions, efficiently capturing alkyl radicals (R·) and peroxy radicals (ROO·) generated by polymer photodegradation, interrupting the chain reaction of photooxidative degradation. The combined use of the two has a significant synergistic effect: UVA reduces the number of initial free radicals initiated by ultraviolet light, alleviating the burden on HALS; HALS captures free radicals that UVA fails to prevent, compensating for the shortcomings of UVA. Furthermore, HALS is recyclable during the reaction process (Denisov cycle), providing long-lasting light stability. The synergistic effect of these two factors significantly enhances the weather resistance of the coating, achieving an artificial aging resistance of over 3000 hours.

[0023] Preferably, the composite filler is obtained by mixing talc, calcium carbonate, and quartz powder in a mass ratio of 1-2:2-4:1. Talc has a flake-like structure, which forms a "maze effect" by stacking layers in the coating film, extending the penetration path of water molecules and corrosive media, and improving the coating film's impermeability. Calcium carbonate has spherical particles that can fill the gaps between the flake-like talc particles, increasing the density of the coating film. Quartz powder has high hardness and good wear resistance, which can improve the wear resistance and scratch resistance of the coating film. The particle size distribution design of the three fillers results in the densest packing inside the coating film, significantly improving the mechanical properties and barrier performance of the coating film.

[0024] Hydrophobically modified polycarboxylate dispersants (such as OROTAN 731A) are sodium salts of hydrophobically modified polycarboxylate copolymers with an ABA block structure. In their molecular structure, the hydrophobic blocks (A-segment) can adsorb onto the surface of filler particles, while the hydrophilic blocks (B-segment) extend into the aqueous phase, achieving efficient filler dispersion through steric hindrance. Simultaneously, the hydrophobic blocks migrate towards the coating-air interface during coating drying, reducing the surface energy of the coating and improving its hydrophobicity and stain resistance. Organosilicon-modified polyether dispersants (such as BYK-190) contain both polyether and organosilicon segments. The polyether segments provide water solubility and dispersibility, while the organosilicon segments provide hydrophobicity and the ability to reduce surface tension. When used in combination, the hydrophobically modified polycarboxylate dispersant is mainly responsible for the efficient dispersion of pigments and fillers and the hydrophobic modification of the coating film, while the organosilicon modified polyether dispersant is mainly responsible for the hydrophobic treatment of the coating film surface and the reduction of surface tension. The two work together to give the coating film excellent hydrophobicity from the inside out, significantly improving the water resistance and stain resistance of the coating film.

[0025] Preferably, the antifreeze is propylene glycol or ethylene glycol.

[0026] Preferably, the thickener is one or more of hydroxyethyl cellulose (HEC), dioctyl phthalate (DOP), and diisononyl phthalate (DINP).

[0027] The defoamer and film-forming aid mentioned can both be conventional products in this field.

[0028] The second objective of this invention is to provide a method for preparing a highly weather-resistant and waterproof coating, comprising the following steps:

[0029] S1. Pretreatment of reactive nano zinc oxide: Reactive nano zinc oxide is reacted with KH-570 in anhydrous ethanol at 60-80℃ for 2-4 hours, filtered and dried to obtain surface-modified reactive nano zinc oxide;

[0030] S2. Preparation of premix: The silicone-acrylic composite emulsion, composite crosslinking agent, silane coupling agent, and methacrylic acid are premixed at 35-45℃ and stirred at 300-500 r / min for 20-30 min to allow the silane coupling agent to undergo a partial pre-crosslinking reaction with the active groups in the emulsion. Then, film-forming aid, ultraviolet light absorber, and hindered amine light stabilizer are added, and stirring is continued for 10-15 min to obtain premix A.

[0031] S3. Preparation of thickening premix: Mix the thickener and antifreeze, stir evenly to obtain thickening premix B;

[0032] S4. Finished product preparation: Slowly add hydrophobic modified dispersant, 1 / 2 of the total amount of defoamer, surface-modified reactive nano zinc oxide, and composite filler to premix A, and stir at 300-400 r / min for 20-30 min to mix evenly. Then add thickening premix B and the remaining defoamer, and stir at 200-300 r / min for 30-40 min. Filter and discharge to obtain a high weather-resistant waterproof coating for metal roofs.

[0033] Preferably, the amount of anhydrous ethanol used in step S1 is 3-5 times the mass of reactive nano zinc oxide; the temperature of the pre-crosslinking reaction in step S2 is 35-45℃ and the time is 20-30 min.

[0034] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) By designing an organosilicon-modified acrylate core-shell composite emulsion, the weather resistance, heat resistance and hydrophobicity of the coating are improved from the base material level. The high bond energy of the Si-O bond gives the coating excellent resistance to UV degradation.

[0036] (2) Through the triple crosslinking network design of reactive nano zinc oxide-silane coupling agent-composite crosslinking agent, the chemical bonding of inorganic nanoparticles, organic polymers and metal substrates is realized, which significantly improves the mechanical properties, heat resistance, water resistance and durability of the coating film.

[0037] (3) By using a compound design of hydrophobic modified dispersants, the coating film is given hydrophobic properties from the inside out while ensuring efficient dispersion of fillers, which significantly improves water resistance and stain resistance.

[0038] (4) By designing a composite light stabilization system of ultraviolet light absorber and hindered amine light stabilizer, the synergistic effect of the two is utilized to greatly improve the weather resistance of the coating film, and the artificial aging resistance time can reach more than 3000h.

[0039] (5) By designing the particle size distribution of talc-calcium carbonate-quartz powder, the filler is packed most tightly, which improves the density and shielding performance of the coating. Detailed Implementation

[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0041] The specific raw material information used in this invention is as follows:

[0042] 1. Silicone-acrylic composite emulsion (organosilicon-modified acrylate core-shell emulsion), solid content 50%, Tg=-30℃, particle size 120nm, B-9328, Badifu Industrial Co., Ltd.

[0043] 2. Hydrophobically modified polycarboxylate dispersant, OROTAN 731A, solid content 25%, viscosity 80 mPa·s, Dow Chemical (China) Co., Ltd.;

[0044] 3. Organosilicon-modified polyether dispersant, BYK-190, solid content 52%, BYK Chemical (China) Co., Ltd.;

[0045] 4. Reactive nano zinc oxide, particle size 30nm, specific surface area 90m² 2 / g, Xuancheng Jingrui New Materials Co., Ltd. JR-NZ50;

[0046] 5. γ-Methacryloxypropyltrimethoxysilane (KH-570), purity ≥97%, Nanjing Liangui Chemical Co., Ltd.;

[0047] 6. γ-aminopropyltriethoxysilane (KH-550), purity ≥97%, Nanjing Liansilicon Chemical Co., Ltd.;

[0048] 7. γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), purity ≥97%, Nanjing Liansilicon Chemical Co., Ltd.

[0049] 8. Triallyl isocyanurate (TAIC), purity ≥98%, industrial grade, Wuhan Organic Industry Co., Ltd.;

[0050] 9. Trimethylolpropane trimethacrylate (TMPTMA), purity ≥95%, industrial grade, Wuhan Organic Industry Co., Ltd.;

[0051] 10,2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole (UV-329), purity ≥99%, BASF (China) Co., Ltd.

[0052] 11. Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (Tinuvin 770), purity ≥98%, BASF (China) Co., Ltd.;

[0053] 12. Talc powder, 1250 mesh, whiteness ≥90%, Guangxi Longsheng Huamei Talc Development Co., Ltd.;

[0054] 13. Calcium carbonate, 800 mesh, whiteness ≥92%, Guangxi Guilin Jinshan Chemical Co., Ltd.;

[0055] 14. Quartz powder, 1000 mesh, SiO2≥99%, Anhui Fengyang Yinghao Quartz Sand Co., Ltd.;

[0056] 15. Organosilicon defoamer, BYK-024, BYK Chemical (China) Co., Ltd.;

[0057] 16. Film-forming aid, Texanol, Eastman Chemical (China) Co., Ltd.;

[0058] 17. Propylene glycol, industrial grade, purity ≥99%; China Petrochemical Corporation Asset Management Co., Ltd.

[0059] 18. Methacrylic acid, purity ≥99%, industrial grade, Shanghai Huayi Acrylic Acid Co., Ltd.

[0060] 19. Hydroxyethyl cellulose thickener (HEC), QP-100MH, Dow Chemical (China) Co., Ltd.;

[0061] 20. Deionized water, conductivity ≤10μS / cm, homemade.

[0062] Example 1

[0063] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0064] Silicone-acrylic composite emulsion (Badfu B-9328) 400 parts, hydrophobically modified polycarboxylate dispersant OROTAN 731A 8 parts, organosilicon modified polyether dispersant BYK-190 2 parts, reactive nano zinc oxide (KH-570 pretreatment) 15 parts, KH-550 3 parts, TAIC 2 parts, TMPTMA 1 part, UV-329 1.0 part, Tinuvin 770 0.5 parts, talc 60 parts, calcium carbonate 100 parts, quartz powder 40 parts, BYK-024 defoamer 3 parts, alcohol ester dodecyl 10 parts, propylene glycol 15 parts, methacrylic acid 3 parts, HEC thickener (QP-100MH) 4 parts, deionized water 120 parts.

[0065] The preparation method includes the following steps:

[0066] S1. Pretreated reactive nano zinc oxide: 15 parts of reactive nano zinc oxide and 0.3 parts of KH-570 were reacted in 60 parts of anhydrous ethanol at 70℃ for 3h, filtered, and vacuum dried at 80℃ for 4h to obtain surface-modified reactive nano zinc oxide.

[0067] S2. Preparation of premix: 400 parts of silicone-acrylic composite emulsion, 2 parts of TAIC, 1 part of TMPTMA, 3 parts of KH-550, and 3 parts of methacrylic acid are premixed at 40°C and stirred at 400 r / min for 25 min to allow KH-550 to undergo a partial pre-crosslinking reaction with the carboxyl groups in the emulsion. Then, 10 parts of alcohol ester dodecyl, 1.0 part of UV-329, and 0.5 parts of Tinuvin 770 are added, and stirring is continued for 12 min to obtain premix A.

[0068] S3. Preparation of thickening premix: Mix 4 parts of HEC thickener with 15 parts of propylene glycol and stir evenly to obtain thickening premix B;

[0069] S4. Finished Product Preparation: Slowly add 8 parts OROTAN 731A, 2 parts BYK-190, 1.5 parts BYK-024 defoamer, surface-modified reactive nano zinc oxide, 60 parts talc, 100 parts calcium carbonate, and 40 parts quartz powder to premix A. Stir at 350 r / min for 25 min to mix evenly. Then add thickening premix B and the remaining 1.5 parts defoamer. Stir at 250 r / min for 35 min. Filter and discharge to obtain a high weather-resistant waterproof coating for metal roofs.

[0070] Example 2

[0071] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0072] Silicone-acrylic composite emulsion (Badfu B-9328) 350 parts, OROTAN 731A 6 parts, BYK-190 2 parts, reactive nano zinc oxide (KH-570 pretreatment) 10 parts, KH-570 4 parts, TAIC 1.5 parts, TMPTMA 0.5 parts, UV-531 0.8 parts, Tinuvin 292 0.4 parts, talc (1250 mesh) 40 parts, calcium carbonate (800 mesh) 130 parts, quartz powder (1000 mesh) 40 parts, BYK-024 defoamer 2 parts, alcohol ester dodecyl 8 parts, propylene glycol 12 parts, methacrylic acid 2 parts, HEC thickener 3 parts, deionized water 100 parts.

[0073] The preparation method is the same as in Example 1, wherein the reaction temperature of step S1 is 60°C and the reaction time is 2h; the pre-crosslinking temperature of step S2 is 35°C and the stirring time is 20min.

[0074] Example 3

[0075] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0076] Silicone-acrylic composite emulsion (Badfu B-9328) 500 parts, OROTAN 731A 12 parts, BYK-190 3 parts, reactive nano zinc oxide (KH-570 pretreatment) 25 parts, KH-560 5 parts, TAIC 3 parts, TMPTMA 2 parts, UV-329 1.5 parts, Tinuvin 770 0.8 parts, talc (1250 mesh) 80 parts, calcium carbonate (800 mesh) 150 parts, quartz powder (1000 mesh) 60 parts, BYK-024 defoamer 4 parts, alcohol ester dodecyl 13 parts, propylene glycol 18 parts, methacrylic acid 4 parts, HEC thickener (QP-100MH) 5 parts, deionized water 140 parts.

[0077] The preparation method is the same as in Example 1, wherein the reaction temperature of step S1 is 80℃ and the reaction time is 4h; the pre-crosslinking temperature of step S2 is 45℃ and the stirring time is 30min.

[0078] Example 4

[0079] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0080] Silicone-acrylic composite emulsion (Badfu B-9328) 450 parts, OROTAN 731A 10 parts, BYK-190 2.5 parts, reactive nano zinc oxide (KH-570 pretreatment) 20 parts, KH-550 3 parts, KH-570 2 parts, TAIC 2.5 parts, TMPTMA 1.5 parts, UV-329 1.2 parts, Tinuvin 770 0.6 parts, talc (1250 mesh) 70 parts, calcium carbonate (800 mesh) 120 parts, quartz powder (1000 mesh) 50 parts, BYK-024 defoamer 3 parts, dodecyl alcohol ester 12 parts, propylene glycol 16 parts, methacrylic acid 3.5 parts, HEC thickener (QP-100MH) 4.5 parts, deionized water 130 parts.

[0081] The preparation method is the same as in Example 1.

[0082] Example 5

[0083] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0084] Silicone-acrylic composite emulsion (Badfu B-9328) 550 parts, OROTAN 731A 14 parts, BYK-190 3.5 parts, reactive nano zinc oxide (KH-570 pretreatment) 30 parts, KH-550 4 parts, KH-560 3 parts, TAIC 3.5 parts, TMPTMA 1.5 parts, UV-329 1.8 parts, Tinuvin 770 0.9 parts, talc (1250 mesh) 100 parts, calcium carbonate (800 mesh) 180 parts, quartz powder (1000 mesh) 70 parts, BYK-024 defoamer 4 parts, alcohol ester dodecyl 15 parts, propylene glycol 20 parts, methacrylic acid 5 parts, HEC thickener (QP-100MH) 5 parts, deionized water 150 parts.

[0085] The preparation method is the same as in Example 1.

[0086] Example 6

[0087] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0088] Silicone-acrylic composite emulsion (Badfu B-9328) 420 parts, OROTAN 731A 9 parts, BYK-190 2.5 parts, reactive nano zinc oxide (KH-570 pretreatment) 18 parts, KH-550 2.5 parts, KH-570 2.5 parts, TAIC 2 parts, TMPTMA 1 part, UV-531 1.0 part, Tinuvin 292 0.5 parts, talc (1250 mesh) 55 parts, calcium carbonate (800 mesh) 110 parts, quartz powder (1000 mesh) 45 parts, BYK-024 defoamer 3 parts, alcohol ester dodecyl 11 parts, propylene glycol 15 parts, methacrylic acid 3 parts, HEC thickener (QP-100MH) 4 parts, deionized water 125 parts.

[0089] The preparation method is the same as in Example 1.

[0090] Example 7

[0091] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0092] Silicone-acrylic composite emulsion (Badfu B-9328) 480 parts, OROTAN 731A 11 parts, BYK-190 3 parts, reactive nano zinc oxide (KH-570 pretreatment) 22 parts, KH-560 6 parts, TAIC 3 parts, TMPTMA 2 parts, UV-329 1.5 parts, UV-531 0.5 parts, Tinuvin 770 0.7 parts, talc (1250 mesh) 75 parts, calcium carbonate (800 mesh) 140 parts, quartz powder (1000 mesh) 55 parts, BYK-024 defoamer 3.5 parts, dodecyl alcohol ester 14 parts, propylene glycol 18 parts, methacrylic acid 4 parts, HEC thickener (QP-100MH) 4.5 parts, deionized water 135 parts.

[0093] The preparation method is the same as in Example 1.

[0094] Example 8

[0095] A highly weather-resistant and waterproof coating for metal roofs comprises the following components in parts by weight:

[0096] Silicone-acrylic composite emulsion (Badfu B-9328) 380 parts, OROTAN 731A 7 parts, BYK-190 2 parts, reactive nano zinc oxide (KH-570 pretreatment) 5 parts, KH-550 2 parts, TAIC 1 part, TMPTMA 0.5 parts, UV-329 0.5 parts, Tinuvin 770 0.3 parts, talc (1250 mesh) 100 parts, calcium carbonate (800 mesh) 150 parts, quartz powder (1000 mesh) 60 parts, BYK-024 defoamer 2 parts, dodecyl alcohol ester 5 parts, propylene glycol 10 parts, methacrylic acid 1 part, HEC thickener (QP-100MH) 3 parts, deionized water 100 parts.

[0097] The preparation method is the same as in Example 1.

[0098] Comparative Example 1 uses ordinary pure acrylic emulsion instead of silicone-acrylic composite emulsion.

[0099] A waterproof coating for metal roofs differs from Example 1 in that 400 parts of silicone-acrylic composite emulsion (Badfu B-9328) are replaced with 400 parts of ordinary pure acrylic emulsion (Badfu RS-998A, solid content 50%, Tg=-30℃), while the remaining components and preparation methods are the same as in Example 1.

[0100] Comparative Example 2: Low content of organosilicon monomers

[0101] A waterproof coating for metal roofs differs from Example 1 in that 400 parts of silicone-acrylic composite emulsion (Badfu B-9328, 10% silicone content) are replaced with 400 parts of silicone-acrylic emulsion with only 2% silicone content (the remaining parameters are the same), while the other components and preparation methods are the same as in Example 1.

[0102] Comparative Example 3: Excessive content of organosilicon monomers

[0103] A waterproof coating for metal roofs differs from Example 1 in that 400 parts of silicone-acrylic composite emulsion (Badfu B-9328, 10% silicone content) are replaced with 400 parts of silicone-acrylic emulsion with 20% silicone content (the remaining parameters are the same), while the other components and preparation methods are the same as in Example 1.

[0104] Comparative Example 4 uses ordinary zinc oxide instead of reactive nano zinc oxide.

[0105] A waterproof coating for metal roofs, differing from Example 1 in that: 15 parts of reactive nano zinc oxide (particle size 30nm, specific surface area 90m²) are used. 2 / g, KH-570 pretreated) was replaced with 15 parts of ordinary zinc oxide (particle size 500nm, specific surface area 5m²). 2 / g (untreated), the remaining components and preparation methods are the same as in Example 1.

[0106] Comparative Example 5 without silane coupling agent

[0107] A waterproof coating for metal roofs differs from Example 1 in that: KH-550 silane coupling agent is not added, and 3 parts of KH-550 are replaced with 3 parts of deionized water in equal amounts. The remaining components and preparation methods are the same as in Example 1.

[0108] Comparative Example 6 without added composite crosslinking agent

[0109] A waterproof coating for metal roofs differs from Example 1 in that: no TAIC and TMPTMA composite crosslinking agent is added, and 2 parts TAIC and 1 part TMPTMA are replaced with 3 parts deionized water in equal amounts. The remaining components and preparation methods are the same as in Example 1.

[0110] Comparative Example 7 uses only a single crosslinking agent, TAIC

[0111] A waterproof coating for metal roofs differs from Example 1 in that it uses only 3 parts of TAIC as a crosslinking agent, does not add TMPTMA, and the remaining components and preparation methods are the same as in Example 1.

[0112] Comparative Example 8 uses a common anionic dispersant instead of a hydrophobic modified dispersant.

[0113] A waterproof coating for metal roofs differs from Example 1 in that 8 parts of OROTAN 731A and 2 parts of BYK-190 are replaced with 10 parts of a common anionic dispersant (Degao Dispers 757W), while the remaining components and preparation method are the same as in Example 1.

[0114] Comparative Example 9 used only hydrophobically modified polycarboxylate dispersant, without the addition of organosilicon modified dispersant.

[0115] A waterproof coating for metal roofs differs from Example 1 in that 8 parts of OROTAN 731A and 2 parts of BYK-190 are replaced with 10 parts of OROTAN 731A (without adding BYK-190), while the remaining components and preparation method are the same as in Example 1.

[0116] Comparative Example 10: No UV absorbers or hindered amine light stabilizers added.

[0117] A waterproof coating for metal roofs differs from Example 1 in that UV-329 and Tinuvin 770 are not added, and 1.0 part of UV-329 and 0.5 part of Tinuvin 770 are replaced with 1.5 parts of deionized water. The remaining components and preparation methods are the same as in Example 1.

[0118] Comparative Example 11 used only ultraviolet light absorbers, without the addition of hindered amine light stabilizers.

[0119] A waterproof coating for metal roofs differs from Example 1 in that only 1.5 parts of UV-329 are added, and Tinuvin 770 is not added. The remaining components and preparation methods are the same as in Example 1.

[0120] Comparative Example 12 used only hindered amine light stabilizers, without the addition of ultraviolet light absorbers.

[0121] A waterproof coating for metal roofs differs from Example 1 in that only 1.5 parts of Tinuvin 770 are added, and UV-329 is not added. The remaining components and preparation methods are the same as in Example 1.

[0122] Comparative Example 13: A single packing system using only calcium carbonate.

[0123] A waterproof coating for metal roofs differs from Example 1 in that 40 parts of talc powder, 100 parts of calcium carbonate, and 60 parts of quartz powder are replaced with 200 parts of calcium carbonate (800 mesh), while the remaining components and preparation methods are the same as in Example 1.

[0124] Comparative Example 14 did not undergo nano-zinc oxide surface pretreatment.

[0125] A metal roof waterproof coating differs from Example 1 in that the reactive nano zinc oxide is not pretreated with KH-570, but is directly added without surface treatment. The remaining components and preparation methods are the same as in Example 1.

[0126] Comparative Example 15 was mixed directly without undergoing a pre-crosslinking reaction.

[0127] A waterproof coating for metal roofs differs from Example 1 in that: in step S2, no pre-crosslinking reaction is performed; the silicone-acrylic composite emulsion, composite crosslinking agent, silane coupling agent, methacrylic acid, film-forming aid, ultraviolet light absorber, and hindered amine light stabilizer are mixed and stirred for 10 minutes at once; the remaining components and preparation methods are the same as in Example 1.

[0128] The metal roof waterproof coatings prepared in Examples 1-8 and Comparative Examples 1-15 were subjected to key performance tests according to JG / T 375-2012 "Acrylic High-Elastic Waterproof Coatings for Metal Roofs" standard, and artificial weathering resistance tests were conducted according to GB / T 1865-2009. The test results are shown in Table 1.

[0129]

[0130] As can be seen from Table 1:

[0131] Comparative Example 1, using ordinary pure acrylic emulsion, exhibited an artificial aging time of only 1200 hours, significantly lower than the 3200 hours of Example 1. Its water absorption rate was 8.5%, far exceeding the 3.2% of Example 1, and its stain resistance was 22%, significantly inferior to the 8% of Example 1. This indicates that organosilicon modification significantly improved the coating's weather resistance, water resistance, and stain resistance, verifying the effectiveness of the high bond energy of Si-O bonds and the hydrophobic surface design of the core-shell structure. The performance of Comparative Example 2 (2% organosilicon content) and Comparative Example 3 (20% organosilicon content) fell between that of Comparative Example 1 and Example 1, indicating that the organosilicon content needs to be controlled within a reasonable range (5%-15%). Too low a content results in insignificant modification effects, while too high a content affects film formation and storage stability.

[0132] Comparative Example 4 uses ordinary zinc oxide instead of reactive nano zinc oxide. The artificial aging resistance time is only 1500h and the adhesion is only 1.4MPa, both of which are significantly lower than those in Example 1. This shows that the high specific surface area and surface activity of reactive nano zinc oxide give it a stronger UV shielding ability and chemical bonding ability with polymers, demonstrating the superiority of reactive nano zinc oxide over ordinary zinc oxide.

[0133] Comparative Example 5, without the addition of a silane coupling agent, exhibited an adhesion strength of only 0.9 MPa, a water absorption rate as high as 9.5%, and a reduced artificial aging resistance time of 2000 h, all significantly inferior to Example 1. This indicates that the silane coupling agent, acting as a "molecular bridge," establishes chemical bonds between the nano-zinc oxide, polymer, and metal substrate, significantly improving the adhesion, water resistance, and durability of the coating.

[0134] Comparative Example 6, without the addition of a composite crosslinking agent, showed a decrease in tensile strength to 2.6 MPa, elongation at break to 310%, and artificial aging time to 1800 h, indicating that the crosslinking agent is crucial for improving the mechanical properties and weather resistance of the coating. Comparative Example 7, using only TAIC crosslinking agent, showed better performance than Comparative Example 6 but lower performance than Example 1, demonstrating a synergistic effect between the combined use of TAIC and TMPTMA. TAIC provides heat resistance and long-term stability, while TMPTMA provides rapid crosslinking and high crosslinking density, with both offering complementary advantages.

[0135] Comparative Example 8, using a common anionic dispersant, exhibited a water absorption rate as high as 9.2%, a stain resistance of 28%, and an artificial aging time of only 1400 hours, all significantly inferior to Example 1. This indicates that the hydrophobic modified dispersant not only plays a dispersing role, but its hydrophobic blocks also migrate to the interface during the coating drying process, significantly improving the hydrophobicity and stain resistance of the coating. Comparative Example 9, using only a hydrophobic modified polycarboxylate dispersant without the addition of an organosilicon modified dispersant, showed performance levels between Comparative Example 8 and Example 1, demonstrating a synergistic effect when the two dispersants are used in combination.

[0136] Comparative Example 10, without any light stabilizer, had the worst artificial aging time of only 800 hours, indicating that light stabilizers are crucial for the weather resistance of the coating. Comparative Example 11, using only a UV absorber, had an artificial aging time of 2200 hours; Comparative Example 12, using only a hindered amine light stabilizer, had an artificial aging time of 2500 hours; while Example 1, using a combination of both, achieved an artificial aging time of 3200 hours, significantly better than any single application. This fully verifies the synergistic effect of UV absorbers and hindered amine light stabilizers: UVA reduces free radical generation at the source, while HALS captures residual free radicals and can be recycled, achieving a synergistic light stabilization effect greater than the sum of its parts (1+1>2).

[0137] Comparative Example 13, using a single calcium carbonate filler, showed a decrease in tensile strength to 2.9 MPa, an increase in water absorption to 7.5%, and a decrease in artificial aging time to 1600 h. This indicates that the combined use of fillers with different shapes and particle sizes, through the "maze effect" of flake talc, the filling and densification of spherical calcium carbonate, and the wear-resistant enhancement of quartz powder, significantly improved the overall performance of the coating.

[0138] Comparative Example 14 did not undergo nano-zinc oxide surface pretreatment, and Comparative Example 15 did not undergo pre-crosslinking reaction. Their performance was significantly lower than that of Comparative Example 1. This indicates that Example 1 achieved chemical bonding of inorganic nanoparticles, organic polymers, and metal substrates through a triple crosslinking network design of reactive nano-zinc oxide-silane coupling agent-composite crosslinking agent, which significantly improved the mechanical properties, heat resistance, water resistance, and durability of the coating film.

[0139] In summary, this invention achieves a comprehensive improvement in the coating's weather resistance, water resistance, stain resistance, mechanical properties, and corrosion resistance through the design of the silicone-acrylate core-shell structure of the silicone-acrylic composite emulsion, the construction of a triple crosslinking network using reactive nano zinc oxide, silane coupling agents, and composite crosslinking agents, the synergistic hydrophobic effect of the hydrophobic modified dispersant, and the compound light stabilization system of ultraviolet light absorbers and hindered amine light stabilizers. All performance indicators are superior to existing technologies, and the artificial aging resistance can reach more than 3000 hours, which can meet the service life requirement of more than 10 years for metal roofs.

[0140] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A highly weather-resistant and waterproof coating for metal roofs, characterized in that, The components include the following parts by weight: The composition includes: 350-550 parts silicone-acrylic composite emulsion, 5-15 parts hydrophobic modified dispersant, 5-30 parts reactive nano zinc oxide, 2-8 parts silane coupling agent, 1-5 parts composite crosslinking agent, 0.5-2 parts ultraviolet light absorber, 0.3-1 parts hindered amine light stabilizer, 200-350 parts composite filler, 2-4 parts defoamer, 5-15 parts film-forming aid, 10-20 parts antifreeze, 1-5 parts methacrylic acid, 3-5 parts thickener, and 100-150 parts deionized water.

2. The high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The silicone-acrylic composite emulsion is an organosilicon-modified acrylate core-shell composite emulsion, which is prepared by seed emulsion polymerization of vinyl-containing organosilicon monomers and acrylate monomers. The organosilicon monomers account for 5%-15% of the total mass of the monomers, the mass ratio of core layer monomers to shell layer monomers is 1:0.8-1.2, the glass transition temperature is -40℃ to -20℃, the solid content is 45%-55%, and the particle size is 80-150nm.

3. The high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The vinyl-containing organosilicon monomer is one or more of vinyltrimethoxysilane and vinyltriethoxysilane; the acrylate monomer is one or more of butyl acrylate, methyl methacrylate, and 2-ethylhexyl acrylate.

4. The high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The hydrophobic modified dispersant is a mixture of hydrophobic modified polycarboxylate dispersant and organosilicon modified polyether dispersant at a mass ratio of 2-4:1; the hydrophobic modified polycarboxylate dispersant is Rohm and Haas OROTAN 731A or Haichuan Chemical HC-5020; the organosilicon modified polyether dispersant is BYK-190 or Dispers 670.

5. A high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The reactive nano-zinc oxide has a particle size of 20-50 nm and a specific surface area greater than 80 m². 2 / g, the surface is pretreated with a silane coupling agent, the silane coupling agent used in the pretreatment is KH-570, and the amount of KH-570 is 1%-3% of the mass of nano zinc oxide.

6. The high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane; the composite crosslinking agent is a mixture of triallyl isocyanate and trimethylolpropane trimethacrylate in a mass ratio of 1-3:

1.

7. A high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The ultraviolet light absorber is one or two of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole and 2-hydroxy-4-n-octyloxybenzophenone; the hindered amine light stabilizer is one or two of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and bis-1,2,2,6,6-pentamethyl-4-piperidinol sebacate; the mass ratio of the ultraviolet light absorber to the hindered amine light stabilizer is 1.5-3:

1.

8. A high weather-resistant and waterproof coating for metal roofs according to claim 1, characterized in that, The composite filler is obtained by mixing talc powder, calcium carbonate, and quartz powder in a mass ratio of 1-2:2-4:

1.

9. The method for preparing the high weather-resistant waterproof coating according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Pretreatment of reactive nano zinc oxide: Reactive nano zinc oxide is reacted with KH-570 in anhydrous ethanol at 60-80℃ for 2-4 hours, filtered and dried to obtain surface-modified reactive nano zinc oxide; S2. Preparation of premix: The silicone-acrylic composite emulsion, composite crosslinking agent, silane coupling agent, and methacrylic acid are premixed at 35-45℃ and stirred at 300-500 r / min for 20-30 min to allow the silane coupling agent to undergo a partial pre-crosslinking reaction with the active groups in the emulsion. Then, film-forming aid, ultraviolet light absorber, and hindered amine light stabilizer are added, and stirring is continued for 10-15 min to obtain premix A. S3. Preparation of thickening premix: Mix the thickener and antifreeze, stir evenly to obtain thickening premix B; S4. Finished product preparation: Slowly add hydrophobic modified dispersant, 1 / 2 of the total amount of defoamer, surface-modified reactive nano zinc oxide, and composite filler to premix A, and stir at 300-400 r / min for 20-30 min to mix evenly. Then add thickening premix B and the remaining defoamer, and stir at 200-300 r / min for 30-40 min. Filter and discharge to obtain a high weather-resistant waterproof coating for metal roofs.

10. The preparation method according to claim 9, characterized in that, The amount of anhydrous ethanol used in step S1 is 3-5 times the mass of reactive nano zinc oxide; the temperature of the pre-crosslinking reaction in step S2 is 35-45℃ and the time is 20-30 min.